2013
DOI: 10.1063/1.4801794
|View full text |Cite
|
Sign up to set email alerts
|

Size effects in the temperatures of phase transitions in KNbO3 nanopowder

Abstract: The paper reports on thorough Raman-scattering study of newly synthesized nanoscale powders of potassium niobate (KNbO3) aimed at evaluating the possible modification of the phase transition temperatures versus the corresponding bulk values. We register a significant expansion of the temperature ranges of all phase transitions, which is attributed to a wide distribution of particle sizes. An average temperature of each phase transition shifts to the high-temperature region differently, namely by 10°, 25°, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Classical examples are unexpected experimental results of Yadlovker and Berger [16,17,18], which reveal the enhancement of polar properties of cylindrical nanoparticles of Rochelle salt. Frey and Payne [19], Zhao et al [20], Drobnich et al [21], Erdem et al [22] and Golovina et al [23,24,25] demonstrate the possibility to control the phase transitions (including new polar phases appearance) for BaTiO3, S2P2S6, PbTiO3 and KTa1-хNbхO3 nanopowders and nanoceramics by finite size effects.…”
Section: Introductionmentioning
confidence: 99%
“…Classical examples are unexpected experimental results of Yadlovker and Berger [16,17,18], which reveal the enhancement of polar properties of cylindrical nanoparticles of Rochelle salt. Frey and Payne [19], Zhao et al [20], Drobnich et al [21], Erdem et al [22] and Golovina et al [23,24,25] demonstrate the possibility to control the phase transitions (including new polar phases appearance) for BaTiO3, S2P2S6, PbTiO3 and KTa1-хNbхO3 nanopowders and nanoceramics by finite size effects.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies of T c evolution in doped KNbO 3 have also been reported [41][42][43][44][45] . as broadened lineshapes, complicating determination of peak positions and mode assignments [42][43][44]46 . Nevertheless, Raman-active mode assignments and transition temperatures in solid solutions such as (K,A)NbO 3 have been made and can also be accomplished in B -site solid solution systems, based on comparison with end members.…”
Section: Introductionmentioning
confidence: 99%
“…Frey and Payne [108], Zhao et al [109], and Erdem et al [110] demonstrated a possibility to control the temperature of a ferroelectric phase transition, as well as the magnitude and position of a dielectric permittivity maximum, for BaTiO 3 and PbTiO 3 nanopowders and nanoceramics. The research of KTa 1− Nb O 3 nanopowders [111] and ceramic nanograins [112][113][114] revealed the emergence of new polar phases and a shift of the phase transition temperature with respect to that in bulk crystals. The size effects were detected in SrBi 2 Ta 2 O 9 nanoparticles by Yu et al [115] and Ke et al [116], by using Raman spectroscopy.…”
Section: Multiferroic Nanoparticles the State Of Artmentioning
confidence: 99%